The View of Empire in Aeneas Sylvius Piccolomini (Pope Pius II) - Toews, John B. (Traditio, 1968)
Aeneas Sylvius Piccolomini (1405–64), the man who succeeded Calixtus III to the apostolic chair in 1458, was destined to become one of the best known pontiffs of the later Middle Ages. His popularity not only rests upon his own extensive literary and historical production, but upon the extensive historical literature subsequently devoted to this fifteenth-century figure. Multiple interpretations and assessments of his character and contributions abound. Caught up in the severe conceptualization of nineteenth-century renaissance scholarship, Aeneas Sylvius emerged as a slightly tarnished dilettante who only partially exemplified the typical Renaissance man with his clear-cut and self-reliant aesthetic and moral characteristics. In this spirit Georg Voigt raised grave suspicions as to Aeneas' integrity in both his private and public life. Jacob Burckhardt, who could only appreciate the pope's multiplicity from the standpoint of the representative artistic types exemplifying Italian humanism, failed to find the ‘whole man’ in the versatile Italian. As historiography moved towards a more diffuse view of the Renaissance and saw it as a shift of balance and change in emphasis rather than an abrupt change, the image of Aeneas Sylvius was gradually freed from such narrow interpretations. The struggle was long and intense for the scholarly tyranny of Voigt, though not always verified by a re-examination of the documents, was argumentatively infectious. Today, a half century of detailed research has added many additional perspectives to our knowledge of Aeneas Sylvius and has clarified many particular problems related to both his earlier life and later pontificate. Future studies will not differ too substantially from this pattern. The inconsistency accompanying the maturation of human character; the conflict between the theological-political values of any one man and the current aspirations of domestic and international ambition; the transitory character of the age—all these factors will continue to hamper assessments of Aeneas Sylvius.